Characterizing treatment‐related patient needs in atopic eczema: insights for personalized goal orientation. (5th November 2019) - Augustin, M.; Langenbruch, A.; Blome, C.; Gutknecht, M.; Werfel, T.; Ständer, S.; Steinke, S.; Kirsten, N.; Silva, N.; Sommer, R.
Abstract: Background: Atopic eczema (AE) is a common and burdensome chronic skin disease. Clinical guidelines suggest an evidence‐based, personalized and stepwise treatment approach. Only few studies have so far focused on the specific patient needs in treatment. Objectives: To characterize therapeutic needs of patients with AE in routine care. Methods: Nationwide cross‐sectional study in 91 dermatology practices and outpatient clinics. Descriptive statistics were used for valuation. Comparisons of HRQoL and general health status were performed including subgroups (age, gender and disease duration). Group comparisons of patient needs were performed for age groups, gender and disease duration. Correlations between patients' needs (PNQ) and HRQoL, generic health status and severity were tested. In addition, a hierarchical regression analysis was performed to determine which variables contribute to explain the variance in patient needs. Results: Analysis of 1678 patients (60.5% female, mean age 38.35 ± 15.92 years) revealed a high disease burden with mean SCORAD of 42.26 ± 18.63, mean DLQI of 8.49 ± 6.45 and mean EQ VAS of 63.62 ± 21.98. Among the patient needs that were most frequently rated as 'quite important'/'very important' were as follows: 'to be free of itching' (96.0%), 'to get better skin quickly' (7.8%) and 'to be healed of all skin defects' (85.7%). In general, older people, women and patients who had been diagnosed with AE for 1 year or less rated the treatment needs as more important than younger patients, men and patients who had been diagnosed with AE for more than 1 year. Major determinants of higher needs were skin‐related quality of life impairments, higher disease severity and higher age. Conclusions: Patients with AE show a high number and variety of therapeutic needs related to disease signs and symptoms, which are associated with individual disease burden. The patient needs vary substantially according to patient characteristics. Identification of patient‐specific needs may support personalized, patient‐centred care and shared decision‐making.